2017
DOI: 10.1159/000466693
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Ovotesticular Disorders of Sex Development in South Africa: A Single-Centre Experience

Abstract: Objective: To describe the clinical characteristics, biochemistry, histopathology, and long-term outcomes in subjects with ovotesticular (OT) disorder of sex development (DSD). Study Design: This is a retrospective subset analysis of 64 cases of histologically confirmed OT DSD. Results: All subjects were South African; 97% (n = 62) were African and 92% (n = 59) were of Zulu ethnicity. The most common karyotype was 46,XX (88%; n = 56), followed by 46,XY (8%), 46,XY/45,X (3%), and 46,XX/46,XY (1%). The median ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 18 publications
2
24
1
Order By: Relevance
“…The incidence of OT DSD ranges from 3-10% of all DSD phenotypes. Variable prevalence of OT DSD was reported worldwide, being noticeably high in black South Africans [van Niekerk, 1976;Ganie et al, 2017]. Our patients had different demographic origins, representing different governorates in Egypt.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The incidence of OT DSD ranges from 3-10% of all DSD phenotypes. Variable prevalence of OT DSD was reported worldwide, being noticeably high in black South Africans [van Niekerk, 1976;Ganie et al, 2017]. Our patients had different demographic origins, representing different governorates in Egypt.…”
Section: Discussionmentioning
confidence: 66%
“…OT DSD has variable presentations, but most commonly, patients present during neonatal period or early childhood with genital ambiguity [Krob et al, 1994;Sircili et al, 2014]. Nevertheless, the clinical presentation in many studies may be delayed worldwide due to poor social conditions and limited access to well-trained medical personnel and advanced investigations [Khadilkar et al, 2015;Ganie et al, 2017]. Ovotestis was reported in worldwide studies to be the most frequent gonad [Krob et al, 1994;Guo et al, 1998;Wiersma and Ramdial, 2009;Ganie et al, 2017;Mao et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study were consistent with the classic literature of 409 cases of true hermaphroditism published by van Niekerk and Retief [1981] regarding karyotype and gonad type in patients with OT-DSD. In both Asian and South African patients, 46,XX is the most common karyotype, accounting for 60.8 and 61.6% of patients in China and Japan, respectively [Matsui et al, 2011], and for 89.1% of patients in South Africa [Ganie et al, 2017]. The vast majority of large sample studies showed that ovotestis was the most common gonadal type, accounting for 40.8-56% [van Niekerk and Retief, 1981;Matsui et al, 2011;Ganie et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
“…In both Asian and South African patients, 46,XX is the most common karyotype, accounting for 60.8 and 61.6% of patients in China and Japan, respectively [Matsui et al, 2011], and for 89.1% of patients in South Africa [Ganie et al, 2017]. The vast majority of large sample studies showed that ovotestis was the most common gonadal type, accounting for 40.8-56% [van Niekerk and Retief, 1981;Matsui et al, 2011;Ganie et al, 2017]. However, among the 22 cases in our hospital, ovotestes (12/44, 27.3%) was only the third common gonadal type and ovary was the most frequent type of gonad (18/44, 40.9%) followed by testis (14/44, 31.8%).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis of 64 OT-DSD cases in South Africa, the most common karyotype was 46,XX (88%), followed by 46,XY (8%), 46,XY/45,X (3%), and 46,XX/46,XY: the male gender was the predominant sex of rearing in two-thirds of the subjects and gender dysphoria was noted in eight patient (11%) at a median of 6.4 years; long follow-up revealed dysphoria in two cases and neuropsychiatric disorders in four cases ( 8 ).…”
mentioning
confidence: 99%